Role of 30 kDa antigen of enteric bacterial pathogens as a possible arthritogenic factor in post-dysenteric reactive arthritis - Malkit Singh; N K Ganguli; Harminder Singh; S D Deodhar; Sunil Sethi; Meera Sharma (Wolters Kluwer Medknow Publications, 2013)
Background: Reactive arthritis (ReA)/Reiter's syndrome (RS) may be caused as a sequel of infections caused by enteric bacterial pathogens, although the mechanisms through, which different pathogens cause similar disease are not clear. Aim: This study was done to look for the presence and role of any common bacterial antigen among the pathogens isolated from such patients. Materials and Methods: A total of 51 patients of ReA and 75 controls (three groups of 25 subjects each: Group 1: Patients who did not develop arthritic complications within 3 months after bacillary dysentery/diarrhea; Group 2: Patients with other arthritic diseases and Group 3: Normal healthy subjects) were included. The isolated enteric pathogens were tested to detect the immunodominant antigens. Results and Conclusions: A common 30 kDa antigen was found to be specifically present among seven arthritogenic enteric bacterial strains belonging to three genera, Salmonella, Shigella and Hafnia. Post-dysenteric ReA patients' sera show higher levels of immunoglobulin G, immunoglobulin M and immunoglobulin A antibodies against this antigen as compared to the controls. Lymphocytes of ReA patients recognize this antigen, proliferate and produce interleukin-2 in response to this antigen more than the lymphocytes of controls. 30 kDa antigen may be a common arthritogenic factor associated with post-dysenteric ReA/RS. The association of Hafnia alvei with post-dysenteric ReA is described for the first time. Four cases of mycobacterial ReA had an association with this antigen, suggesting that the arthritogenic antigen of mycobacteria and enteric bacteria may be of a similar nature.